Design of an Automatic Nutrition System for Hydroponic Plants with an IoT-based NodeMCU Microcontroller - Ridwan Maulana; Aryo De Wibowo Muhammad Sidik (FIDELITY : Jurnal Teknik Elektro, 2019)
An automatic system for hydroponic plants with a flow system with NodeMCU as the brain of the tool. The tool that has been created will work when the NodeMCU gets a WiFi connection to receive and process data. The TDS (Total Dissolved Solids) sensor detects the value of the dissolved solids content in the form of ppm (parts per million), and the ultrasonic sensor detects the level of nutrient liquid in the form of high and low indicators. Then the sensor will send data to the NodeMCU; after processing, the data will be sent to the Blynk application server. In the Blynk application, we can monitor the value of nutrient content and nutrient fluid levels via a smartphone. When the TDS sensor valve reads that the nutrient content is below 560 ppm, the solenoid valve will open after the nutrient content has exceeded the value of 840 ppm, and it will close again. In addition to input in the form of sensors that change the condition of the solenoid valve, we can also operate the solenoid valve through the Blynk application interface. The design of this automatic nutrition system is based on the nutritional value needs of the lettuce plant. The dietary requirements of lettuce are 560 ppm to 840 ppm. Implementing this system is hoped to help farmers monitor the condition of hydroponic plants.